Opportunistic candidates and knowledgeable voters: A recipe for extreme views - David Benček (Kiel Institute for the World Economy (IfW), 2016)
In recent years, a number of Western industrialized nations have experienced a notable polarization of political ideologies, and growing numbers of individuals seemingly support extreme positions. As a result, established political parties have moved to the left or right and new parties have appeared on the fringes. But why are people with extreme political views this visible in the public debate, and how are they able to move party positions further to the margins when they should be outnumbered by a moderate majority? Contradictory to the classic literature that focuses on collective action problems, this paper studies emerging effects from informational asymmetries. It extends a spatial voting model to include incompletely informed candidates and knowledgeable voters. Agent-based simulations suggest that only fringe voters benefit from distorting their opinions and dominating political discourse. At the same time, better informed candidates have a competitive advantage in elections no matter how strongly voters distort their positions.
Keywords: C63; D02; D72; 330; spatial voting; heterogeneous actors; extreme opinions; agent-based modelling